Bauhinia wallichii J.F. Macbr. (Leguminosae-Caesalpinioideae), a species new to Thailand - Saksuwan Larsen, Supee (Thai Forest Bulletin (Botany), 2014)
Bauhinia wallichii (Leguminosae-Caesalpinioideae) is newly recorded from Thailand. The species is described and illustrated.